1972
DOI: 10.1104/pp.49.5.700
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Status and Mycorrhizal Enhancement of Water Transport in Soybean

Abstract: MATERIALS AND METHODSMycorrhizal soybean (Glycine max L. Merr. var. plants have lower resistances to water transport than nonmycorrhizal plants after 4.5 weeks of growth. Although resistances of whole plants differ by 40 %, there were no differences in the resistances of stems plus leaves, indicating that the major effect of the mycorrhizae was to reduce the resistance of the roots. Since the fungitoxicant, p-chloronitrobenzene, had no effect on resistances to water transport, reduced resistances were probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0
3

Year Published

1979
1979
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(76 citation statements)
references
References 25 publications
6
67
0
3
Order By: Relevance
“…Comparisons of root hydraulic conductivities both in P-deficient and P-fertilized non-mycorrhizal and VAM plants by Safir, Boyer & Gerdemann (1972) and Graham & Syvertsen (1984) led to the conclusion that it was enhanced P status of VAM plants which accounted for greater root conductivities. However, the present study emphasizes the importance of extraradical hyphae in water uptake and it is suggested that the reported eliminations of differences in VAM and non-mycorrhizal root water uptake with increased P fertilization may have been due in part to reductions in the quantity of extraradical hyphae which occur under conditions of high P availability (Bethlenfalvay, Bayne & Pacovsky, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of root hydraulic conductivities both in P-deficient and P-fertilized non-mycorrhizal and VAM plants by Safir, Boyer & Gerdemann (1972) and Graham & Syvertsen (1984) led to the conclusion that it was enhanced P status of VAM plants which accounted for greater root conductivities. However, the present study emphasizes the importance of extraradical hyphae in water uptake and it is suggested that the reported eliminations of differences in VAM and non-mycorrhizal root water uptake with increased P fertilization may have been due in part to reductions in the quantity of extraradical hyphae which occur under conditions of high P availability (Bethlenfalvay, Bayne & Pacovsky, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…en el caso de Leucaena sembrada en la costa de chiapas, también se obtuvieron resultados semejantes (aguirre-medina y Velazco 1994). Safir et al (1972) señalan que los hongos micorrízicos incrementan las concentraciones de n y ca, y ames (1987) demostró el transporte del nitrógeno por las hifas de las micorrizas.…”
Section: Contenido De Fósforo Nitrógeno Y Calciounclassified
“…Daft and Okusamya (1973) reported an increased number of vascular bundles in maize following mycorrhizal infection which could reduce resistance to water transport. Safir et al (1972) estimated that root resistance to water uptake was reduced 40% by mycorrhizal infection in soybean. They also noted that phosphate fertilizers reduced root resistance and attributed the improved water transport to improved nutritional status, especially phosphorus.…”
Section: Photosy N Thesismentioning
confidence: 99%
“…Christensen, 1977; Allen, personal observations). Infection with VA mycorrhizae has been shown to enhance water status in soybean (Safir, Boyer and Gerdemann, 1972), onion (Mosse and Hayman, 1971), citrus (Levy and Krikun, 1980) and to improve survival of Atriplex canescens in arid mine spoils (Aldon, 1975). However, only a few investigators have considered possible physiological mechanisms which could contribute to these effects.…”
Section: Photosy N Thesismentioning
confidence: 99%
See 1 more Smart Citation